PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN PRESTASI BELAJAR AKUNTANSI DENGAN MATERI MENYUSUN JURNAL PENYESUAIAN DAN KERTAS KERJA PERUSAHAAN JASA PADA SISWA KELAS XI IPS 2 DI SMA NEGERI 2 BARABAI TAHUN PELAJARAN 2013/2014 - Fakhriani Fakhriani (JURNAL SOCIUS, 2013)
This research aimed at (1) improving students achievement through the application of a learning cooperative model  of Teams Games Tournament (TGT) type, (2) describing the use of a learning cooperative model  of Teams Games Tournament (TGT) type, (3) increasing the motivation for students’ achievement in learning accounting in XI Sosial Science 2 SMA Negeri 2 Barabai years lesson 2013/2014. This research was designed and carried out by using Classroom Action Research (PTK). The result of the research shows that (1) learning achievements of Accounting subject from students of class XI Social Science 2 SMA Negeri 2 Barabai Academic Year 2013/2014 can be improved through Team Games Tournament (TGT) with learning exhaustiveness of 87.10%. (2) the liveliness of the students generally shows good result;and (3) The learning management result of the Teams Games Tournament in general can be assessed as good  Key Word:   Cooperative Learning  Model of Teams Games Tournament (TGT) Type, Achievement Learning, Accounting.